(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article investigates the problems of seismic safety of soil hydraulic structures, which can be destroyed in case of possible earthquakes. The issue of dam safety is of particular relevance, which at present in many states can lead to serious social, economic and environmental consequences.